Design and performance aspects of a custom-built ambient pressure photoelectron spectrometer toward bridging the pressure gap: oxidation of Cu, Ag, and Au surfaces at 1 mbar O-2 pressure - Roy, Kanak; Vinod, C. P.; Gopinath, Chinnakonda S. (Journal of Physical Chemistry C, 2013)
The critical features of a custom-built laboratory version ambient pressure photoelectron spectrometer (Lab-APPES) are presented. A double front cone differential pumping arrangement and an aperture free design employed in the electrostatic lens regime improve the data collection and data quality. In contrast to the conventional X-ray photoelectron spectrometers (XPS) operating at ultrahigh vacuum (UHV), it is possible to explore the electronic structure of solid surfaces under working conditions or closer to working conditions with Lab-APPES. Especially surface-dependent phenomena can be explored up to 1 mbar pressure and up to 873 K by conventional heating methods and at least up to 1273 K by a laser heating method. Simultaneous XPS and reaction kinetic measurements on solid surfaces make the Lab-APPES an important tool to measure the dynamic electronic structure changes on material surfaces under reaction conditions. The interaction of O-2 with polycrystalline foils of Cu, Ag, and Au from UHV to 1 mbar and up to 773 K has been studied.

Demonstration of synergistic catalysis in Au@Ni bimetallic core-shell nanostructures - Vysakh, A. B.; Babu, Chinchu Lizen; Vinod, C. P. (Journal of Physical Chemistry C, 2015)
Coreshell bimetallic nanoparticles comprised of gold core and varying nickel shell have been synthesized, and their synergistic effect in catalysis is explored through catalytic hydrogenation of p-nitrophenol and p-nitrothiophenol. A clear evidence for synergism in Au@Ni core-shell nanoparticles having an ultrathin Ni shell (1-2 nm) around a Au core (6-10 nm) resulting in enhanced catalytic activity is observed. The rates observed from a thin nickel shell are higher than monometallic Au or Ni nanoparticles of similar size or with a thicker Ni shell of 6-8 nm.

Diverse reactivity trends of Ni surfaces in Au@Ni core-shell nanoparticles probed by near ambient pressure (NAP) XPS - Bharathan, Vysakh A.; Jain, Ruchi; Gopinath, Chinnakonda S.; Vinod, C. P. (Catalysis Science & Technology, 2017)
A mild temperature sequential reduction method in aqueous medium is reported for the synthesis of Au@Ni nanoparticles with a core-shell morphology. The nickel shell thickness with a gold core in the nanostructure can be tuned from 2 nm up to about 10 nm. Near ambient pressure XPS (NAPXPS) studies under oxygen atmosphere show that Au-80@Ni-20 with an extremely thin nickel shell (similar to 2 nm) follows a distinctly different decomposition pathway of metastable Ni(OOH) species compared to those with larger shell thickness which behave more like individual nickel surfaces. Thus, Ni(OOH) on Au-80@Ni-20 decomposes to metallic Ni at 100 degrees C and is found to resist oxidation at 0.1 mbar oxygen at this temperature. Those with a larger nickel shell thickness behave more like monometallic Ni in terms of their decomposition and oxidation properties. The Au@Ni system with an ultra thin metallic nickel overlayer (2 nm) shows high catalytic activity and selectivity for phenylacetylene hydrogenation under mild conditions which outweighs their monometallic counterparts and those with higher nickel shell thickness.

Dynamics in amine-functionalized mesoporous hybrid materials probed through deuterium magic angle spinning NMR and molecular dynamic simulations - Veena, V. S.; Kavya, I; Lazar, A.; Vinod, C. P.; Ajithkumar, T. G.; Jayanthi, S. (Journal of Physical Chemistry C, 2020)
We present a deuterium magic angle spinning (MAS) NMR study on two widely used hybrid materials (3-glycidyloxy propyl)trimethoxysilane (3-GPTMS) and 3-(trimethoxysilyl)propyl methacrylate (3-MATMS) grafted on SBA-15. Methylene-deuterated diamine as a pendent group is anchored to GPTMS (O3Si-CH2-CH2-CH2-O-CH2-CH(OH)- CH2-NH-CD2-CD2-NH2) and MATMS (O3Si-CH2-CH2-CH2-O-C(N-CD2-CD2-NH2)-C(CH3)=-CH2) postgrafting. Proton and deuterium solid state NMR experiments under MAS were performed at two hydration levels and temperatures ranging from 253 to 315 K. Deuterium spectra were deconvoluted into three A Dr, components with different average quadrupolar parameters: a relatively rigid component arising from local or librational motion of C-H-2(2) corresponding to ``small angle'' jumps, an intermediate dynamic component, and a large amplitude dynamic component. Population ratios of rigid versus dynamic components show that diamine-MATMS is more rigid when compared with diamine-GPTMS at high hydration. The role of the length of the linkers, steric hindrance, grafting concentration, etc. in defining mobility is investigated. Finally, by correlating proton and deuterium MAS NMR spectral analysis, the role of a few water molecules in inducing dynamics of the linkers was investigated. Molecular dynamic (MD) simulations support the experimental analysis. MD simulations indicate different types of mobility arising from the same molecular binding configuration of diamine-MATMS. Dynamics induced by a few hydroxyls on the pore surface accessible to the linker, various molecular conformations, and stabilization of the linker through hydrogen bonding with the surface, derived from MD simulations, are discussed.

Direct conversion of methane to formic acid over Au-Fe-NaZSM-5 at ambient pressure using H2O2 - Kumar, Pawan; Ahangar, Iqra; Kesarwani, Srishti; Urkude, Rajashri; Patil, Nita A. R.; Niphadkar, Prashant; Bokade, Vijay V.; Haider, M. Ali; Vinod, C. P. (Catalysis Science & Technology, 2026)
Direct conversion of methane to value-added products is a long-standing challenge. This report presents the one-step conversion of methane to oxygenates using H2O2 as an oxidant over an Au and Fe supported on NaZSM-5 (0.1Au0.1FeNZ) catalyst, which produces 4264 mu mol of oxygenates with 89% selectivity toward formic acid at 10 bar and 60 degrees C within 30 min in a batch process. The catalyst also produces 26.5 mu mol of oxygenates with 70% selectivity for formic acid at atmospheric pressure and 80 degrees C in a continuous flow process over 9 h of reaction time, making it the first report of such a process. The synergistic interaction of Au and Fe, with the crucial role of Na ions in the zeolite framework in driving the reaction, is revealed through various characterization tools like TEM, XPS, and XAS. Theoretical studies elucidate the active sites responsible for lowering the activation barrier for the crucial C-H activation step. Thus, the catalyst enables the conversion of methane into formic acid with high activity and selectivity, offering new possibilities for harnessing this potent greenhouse gas under process-friendly conditions that were previously unexplored.